Praktictí lékari na pocátku transformace zdravotnictví - Zavázalová, H; Bremer, C; Motán, J; Zaremba, V; Vozehová, S (Casopis lekaru ceskych, 1997)
The authors assessed in 68 general practitioners by means of questionnaires selected data on the position in medical practice, satisfaction with it, on the extent, forms and opportunities of further training. All respondents systematically extended their education and training, 97% were keen to master and use new procedures. 37% were satisfied with their practice. They worked on average 50 hours per week and examined on average 236 patients per week in their surgery. On average they referred 11% of their patients to a specialist. Health authorities should participate more in the solution of some problems of general practitioners.
Keywords: Family Practice; Attitude of Health Personnel; průzkumy a dotazníky; rodinné lékařství; Humans; pracovní uspokojení; postoj zdravotnického personálu; Job Satisfaction; reforma zdravotní péče; Czech Republic; Health Care Reform; Surveys and Questionnaires; lidé; Česká republika